Inkluzja edukacyjna na etapie przedszkola w rozumieniu rodziców dzieci niepełnosprawnych - Iwona Myśliwczyk (Problemy Wczesnej Edukacji)
In the field of education we observe many positive changes in equalising educational opportunities for children and young people with disabilities. The most important changes have led to the inclusive paradigm which posits education of disabled children together with children with special educational needs. The article deals with issues related to educational inclusion, variously understood by parents of disabled children. Parents experiencing the disability of their children tend to normalize their lives, including education in a mainstream kindergarten. When talking about their children’s education, they unveiled personal meanings given to this event, showed their individual truths and the reality they experience. The stories they told were given a subjective meaning, which from their perspective is important and shapes their being.